Sections of Angles and $n$th Roots of Numbers - Heineken, H. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
It is known since Galois that an algebraic equation can be solved using suitable nth roots whenever the corresponding Galois group is soluble. The object of this note is to construct real numbers with the use of the nth parts of suitable angles and to state necessary and sufficient conditions for this to be possible.